2014
DOI: 10.1039/c3tx50075f
|View full text |Cite
|
Sign up to set email alerts
|

Bicontinuous cubic phase nanoparticle lipid chemistry affects toxicity in cultured cells

Abstract: Gaining an increased understanding of the toxicity of new lipid nanoparticle formulations such as the class of cubic and hexagonal phase forming nanomaterials called cubosomes™ and hexosomes™ is crucial for their development as therapeutic agents. Surprisingly, the literature on the in vitro and in vivo toxicity of cubic and hexagonal phase forming lipid nanoparticles is negligible, despite a rapidly growing number of publications on their potential use in various therapeutic applications. In this work we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
103
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 62 publications
16
103
3
Order By: Relevance
“…The highest ROS activity per unit area was observed for 30 nm TiO 2 particles, whereas, the trend for crystal phase was amorphous followed by anatase, anatase-rutile mixture and rutile. Similar observations of crystal phase, chemical composition and size were also reported by other research groups [112114]. To minimize the toxicity of nanoparticles, either biocompatible base materials or surface modification by several surface coating agents must be used and are discussed in the following section of this article.…”
Section: Morphological and Physicochemical Characterizationsupporting
confidence: 66%
“…The highest ROS activity per unit area was observed for 30 nm TiO 2 particles, whereas, the trend for crystal phase was amorphous followed by anatase, anatase-rutile mixture and rutile. Similar observations of crystal phase, chemical composition and size were also reported by other research groups [112114]. To minimize the toxicity of nanoparticles, either biocompatible base materials or surface modification by several surface coating agents must be used and are discussed in the following section of this article.…”
Section: Morphological and Physicochemical Characterizationsupporting
confidence: 66%
“…It has a larger surface area to interact with biological membranes with high fluidity, and greater amounts of drugs can be incorporated independent of their solubility. In contrast to our findings, other studies have demonstrated the presence of cubosomes using different types of LCforming lipids such as glyceryl monooleate GMO or phytantriol PHT 10,22 . We strongly believed that several factors might affect the phase structure of LC formulations, such as temperature, type of LC-forming lipid, physiochemical properties of the entrapped drugs, lipid concentration, and type of surfactant.…”
Section: Discussioncontrasting
confidence: 55%
“…38 However, in order to design a more effective drug delivery carrier, it is essential to understand the phase behavior of MO under the inuence of factors such as temperature, chemical environment, water content, and charge. 43 The results showed that MO cubosomes affected the viability of Chinese hamster ovary (CHO) and human alveolar basal epithelial (A549) cell lines differently. 39 It is interesting that only a small number of studies have focused on investigating the toxicity of nanoparticle dispersions made from lyotropic liquid crystal phase forming lipids.…”
Section: Introductionmentioning
confidence: 99%